ENTERING SHANGHAI FREE TRADE ZONE: FROM MALAYSIA’S BUSINESSMEN PERSPECTIVE - Lee Peng- Foo; Mui Yin- Chin; Swee Chin- Ng; Xinjun- Lei; Xiaodi-Zhang; Jia- Wang (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2023)
China’s Belt and Road Initiative (BRI), introduced in 2013, has been strongly supported by various Free Trade Zones (FTZs). The pilot Shanghai Free Trade Zone (SFTZ) received much attention after a major reform in 2019. Malaysia’s enterprises consist of young and infant industries. Hence, this study has aimed to provide insights into the awareness among Malaysia’s enterprises towards SFTZ. In addition, hidden opportunities and challenges will be discussed in detail and further enlighten the concerns of Malaysian enterprises. A purposive sampling method has been applied to select the participants for the five focus group discussions. The results indicated a gap between government practices and industry players regarding the opportunities, challenges, and prospects in the SFTZ. Malaysia is expected to benefit from the SFTZ through comparative advantages in certain industries, with its talent, and through unique products with intellectual property rights. At the same time, Malaysian businesses have remained constrained by several obstacles, such as lack of information, exit policies and differences in regulations. Although MATRADE has stepped in as a bridge between local and Shanghai enterprises, more is needed to be done.